Committed Remembering Native Kinship in and beyond Institutions - Burch, Susan (Critical Indigeneities, 2021)
Between 1902 and 1934, the United States confined hundreds of adults and children from dozens of Native nations at the Canton Asylum for Insane Indians, a federal psychiatric hospital in South Dakota. But detention at the Indian Asylum, as families experienced it, was not the beginning or end of the story. For them, Canton Asylum was one of many places of imposed removal and confinement, including reservations, boarding schools, orphanages, and prison-hospitals. Despite the long reach of institutionalization for those forcibly held at the Asylum, the tenacity of relationships extended within and beyond institutional walls. In this accessible and innovative work, Susan Burch tells the story of the Indigenous people-families, communities, and nations, across generations to the present day-who have experienced the impact of this history. Drawing on oral history interviews, correspondence, material objects, and archival sources, Burch reframes the histories of institutionalized people and the places that held them. Committed expands the boundaries of Native American history, disability studies, and U.S. social and cultural history generally.